1982
DOI: 10.1051/jphys:01982004303053900
|View full text |Cite
|
Sign up to set email alerts
|

On experimental attenuation factors of the amplitude of the EXAFS oscillations in absorption, reflectivity and luminescence measurements

Abstract: This paper is reviewing a number of artefactual limitations in the current EXAFS analysis. In conventional absorption measurements, the major sources of errors are the transmission of harmonics by the monochromator and inevitable leakages of radiation around or through the sample. The consequences are an alteration of the amplitude of the signal but also some harmonic distortion of the EXAFS oscillations and a systematic perturbation of the measured Debye-Waller terms. An efficient correction of the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(91 citation statements)
references
References 19 publications
2
89
0
Order By: Relevance
“…The x-ray-absorption spectra for right and left circularly polarized x-ray beams were done assuming semiinfinite samples, but taking into account the various background contributions (fluorescence of subshells and matrix as well as coherent and incoherent scattering), the angle of incidence of the x-ray beam, and finally the solid angle of the detector [46][47][48].…”
Section: Methodsmentioning
confidence: 99%
“…The x-ray-absorption spectra for right and left circularly polarized x-ray beams were done assuming semiinfinite samples, but taking into account the various background contributions (fluorescence of subshells and matrix as well as coherent and incoherent scattering), the angle of incidence of the x-ray beam, and finally the solid angle of the detector [46][47][48].…”
Section: Methodsmentioning
confidence: 99%
“…2) the fundamental absorption coeflicient from the measured one by using the following equation: monic elimination. The higher harmonics (above the fundamental one) produce more distortion of the EXAFS signal than the lower ones [1][2][3]. Only 6% of the third harmonic intensity (see Fig.…”
Section: General Stepmentioning
confidence: 99%
“…Commonly suggested methods with the use e.g. of total reflection Au mirrors or direct computational methods [1] require knowledge of the mass absorption coefficients for investigated substance and additional structural data (as exact chemical composition, density etc.). It is shown that the existence of high harmonics in the spectrum requires correction especially for samples with a high atomic number.…”
Section: Corrections On the "Sample Holes"mentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra have been corrected for self-absorption effects and for incomplete circular polarization rates of incident x-ray photons. The self-absorption corrections were done in the semi-infinite sample approximation, taking into account the chemical composition, the density, the background contributions (fluorescence of subshells and matrix, coherent and incoherent scattering), and the geometrical factors [29][30][31] . The Np edge-jump intensity ratio M 5 /M 4 has been normalized to 1.57, the value reported in the XCOM tables by Berger et al in Ref.…”
Section: F Xmcd Spectramentioning
confidence: 99%